Avaliação nutricional em crianças internadas em hospitais públicos do estado do Espírito Santo: Atuação da equipe multidisciplinar de terapia nutricional - Janine Pereira da Silva (2010)
Introduction: Despite the existence of specific legislation on nutrition therapy in hospitalized patients, there are just a few studies evaluating the compliance with current legislation and the impact of the Multidisciplinary Team for Nutritional Therapy (MTNT) in anthropometrics and nutritional diagnosis. Dont know the nutritional status at admission may lead to higher risk and worsen the nutritional prognosis and thepatient`s underlying disease. Objectives: To evaluate the nutritional status of admitted children at public hospitals in the State of Espírito Santo, to investigate the role of the MTNT in obtaining and registering in the charts the anthropometric variables and nutritional diagnosis andidentify the accredited hospitals for the practice of nutritional therapy in the State. Methods: A descriptive, prospective inclusion of children admitted to public hospitals of Espírito Santo, in the period from May to July of 2009. Were collected information regarding registration of patient records, admission, anthropometry, nutritional diagnosis, total calorie needs and offered calories, and got the weight, height and head circumference of the sample. The data relating to the actions of the MTNT were obtained by applying a standardized questionnaire and data from accredited hospitals for nutritional therapy obtained on the Ministry of Health`s website and complemented by the state Sanitary Surveillance Agency. The study was approved by the Ethics in Research Committee of the Hospital Infantil Nossa Senhora da Glória - Vitória / ES and the Federal University of Minas Gerais. Results: Out of the 97 hospitals with pediatric beds, only 36 were accredited to nutritional therapy. We evaluated 142 children in seven public hospitals in the state. There was male predominance (60.6%), median age of 1.39 ± 1.37 years andpneumonia diagnosis on admission (12.7%). The prevalence of underweight and low height was 5.6 and 19.0% for the index W / H and H / A, respectively. Despite the high prevalence of nutritional deficiencies, the record of nutritional diagnosis at the admission at the hospital was only observed in 26/142 (18.3%) of the charts. Aside from weight, there was a significant association between enrollment in medical records of the variables and the existence of MTNT. Out of the seven hospitalsevaluated, only one had the MTNT acting as required in legislation on nutritional therapy. Conclusion: A few hospitals are accredited in the Espírito Santo for nutritional therapy. In this population, were observed a high prevalence of injury and lack of nutrition in the medical records of anthropometric data, except weight, often estimated, and the nutritional diagnosis. Among the evaluated hospitals, only one has demonstrated an active MTNT. Such findings reinforce the idea of the breach of legislation relating to nutritional therapy in hospitalized patients.